KONSEP “EFISIENSI-BERKEADILAN DALAM DEMOKRASI EKONOMI MENURUT PASAL 33 AYAT (4) UUD NRI 1945 DALAM PERSPEKTIF PERLINDUNGAN BAGI USAHA KECIL - Bustamin Nongtji (Faculty of Law, Universitas Diponegoro, 2013)
Abstract Prohibition or restriction is necessary for large enterprises as legal safeguards for small businesses. It has been defined in the Act No. 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, which is also set out in Article 33 of the Constitution of the Republic of Indonesia of 1945 in which the state holds a national economy based on economic democracy. Article 33 paragraph (4) NRI 1945 Constitution states that: